Analysis of the field tests efficiency of indoor environmental control and energy saving technology: the cases of Solar Decathlon China 2018. Issue 3 (September 2019) - Zhao, Haitian; Lin, Borong; Zhu, Yingxin; Zhang, Jinghua; Sun, Hongli
Abstract: The International Solar Decathlon initiated by the US Department of Energy in 2002 has been conducted for 17 years, but the literature on the use of field test big data to study the performance of design projects during the competition is scarce. This paper summarizes energy saving technologies used in past Solar Decathlons in the literature. The indoor environment test data of 5 demo participating teams of Solar Decathlon China (SDC) 2018 are organized and analyzed. The energy consumption and indoor environment data of buildings of SDC 2018 are comprehensively compared with those of past solar competition buildings. The energy consumption characteristics and indoor thermal environment characteristics of this zero-energy building are summarized. An energy evaluation index for unit energy consumption, namely energy consumption per square meter per day, is proposed. The unit energy consumption of buildings during the solar competition is 0.28–0.51 kWh/(d⋅m 2 ), with an average of 0.35 kWh/(d m 2 ). HVAC system energy consumption exceeds 50%. The unit energy consumption of the air conditioning system ranges between 0.13–0.23 kWh/(d⋅m 2 ) with an average of 0.18 kWh/(d⋅m 2 ). This can be used as a reference for future solar energy system capacity designs. According to the results of the analysis of the competition data, the recommendations for the construction of zero-energy houses for intermittent use are given in the design of the architecture design and the HVAC system. Furthermore, a control strategy to ensure indoor environment comfort and system energy saving has also been proposed.